Exploration of the mechanism of Taohong Siwu Decoction for the treatment of ischemic stroke based on CCL2/CCR2 axis - Li, Jingjing; Zhang, Lijuan; Xue, Sujun; Yu, Chao; Li, Yumeng; Li, Shuangping; Ye, Qingping; Duan, Xianchun; Peng, Daiyin (Frontiers in Pharmacology, 2024)
Background and aims: Taohong Siwu Decoction (THSWD) is a traditional Chinese herbal prescription that is effective for ischemic stroke, Whether THSWD regulates the CCL2/CCR2 axis and thus reduces the inflammatory response induced by ischemic stroke is not known.The aim of this study was to elucidate the mechanism of action of THSWD in the treatment of ischemic stroke using bioinformatics combined with in vitro and in vivo experiments. Methods: R language was used to analyze middle cerebral artery occlusion/reperfusion (MCAO/R) rat transcriptome data and to identify differential gene expression following THSWD treatment. Gene set enrichment analysis (GSEA) was used to analyze the gene set enrichment pathway of MCAO/R rats treated with THSWD. PPI networks screened key targets. The Human Brain Microvascular Endothelial Cells (HBMEC) Oxygen Glucose Deprivation/Reoxygenation (OGD/R) model and SD rat models of MCAO/R were established. FITC-dextran, immunofluorescence, flow cytometry, ELISA, immunohistochemistry, western blotting, and RT-qPCR were performed to identify potential treatment targets. Results: A total of 515 differentially expressed genes of THSWD in MCAO/R rats were screened and 92 differentially expressed genes of THSWD potentially involved in stroke intervention were identified, including Cd68, Ccl2, and other key genes. In vitro, THSWD reversed the increase in permeability of HBMEC cells and M1/M2 polarization of macrophages induced by CCL2/CCR2 axis agonists. In vivo, THSWD improved nerve function injury and blood-brain barrier injury in MCAO/R rats. Further, THSWD inhibited the infiltration and polarization of macrophages, reduced the expression of IL-6, TNF-α, and MMP-9, and increased the expression of IL-4, while reducing the gene and protein expression of CCL2 and CCR2. Conclusion: THSWD may play a protective role in ischemic stroke by inhibiting the CCL2/CCR2 axis, reducing the infiltration of macrophages, and promoting the polarization of M2 macrophages, thereby reducing inflammatory damage, and protecting injury to the blood-brain barrier.